Animals as Part of the Compositional Strategy in Aratus’ Phaenomena - Garbačiauskas, Paulius (Literatūra, 2018)
[full article, abstract in English; abstract in Lithuanian]This paper is focused on the compositional features of Aratus’ Phaenomena and the poet’s strategy in proportioning astronomical and meteorological material. Apparently uneven as they are, two principal parts of the poem pose certain difficulties regarding the general importance of the meteorological signs and their relation to the astronomical ones. It seems that animals, playing their role in both parts of the Phaenomena, and both types of visible signs (i.e., as virtual shapes of heavenly bodies and real, terrestrial creatures) can provide a certain integrating key and better understanding of the poet’s strategic decisions in shaping the Phaenomena as a solid and seamless peace of poetry.
Keywords: Aratus, Phaenomena, Prognostica, astronomy, meteorology